PROGRAMS OF AES EPHEMERIDES CALCULATION - Kolesnik, S. Ja.; Paltsev, N. G. (Одеські астрономічні публікації, 2017)
A program of AES ephemerides calculation is developed which permits, from the given set of elemental orbit, to calculate ephemerides for several months’ period.